LOCATION AND COMPOSITION OF SPORE MUCOPEPTIDE IN BACILLUS SPECIES - Warth, A. D. (The Rockefeller University Press, 1963)
Spore integuments of Bacillus coagulans were prepared containing nearly all the hexosamine and α, ε-diaminopimelic acid (DAP) present in intact spores. Subsequent autolytic action resulted in the destruction and removal of the residual cortical structure and "cortical membrane" leaving the appearance of the inner and outer spore coats unchanged in electron micrographs. Concurrently, all the hexosamine and DAP in the preparation was released mainly as non-diffusible mucopeptide containing alanine, glutamic acid, DAP, and all the glucosamine and muramic acid. Some diffusible peptides containing alanine, glutamic acid, and DAP were also present but there was little protein or carbohydrate. Lysozyme digestion of integument preparations from heated spores of Bacillus 636, B. subtilis, B. coagulans, and B. stearothermophilus specifically removed the residual cortex and cortical membrane with the release of the mucopeptide. In B. cereus T, only the residual cortex and part of the mucopeptide were solubilized by lysozyme. The effect of several reagents and enzymes upon the appearance and removal of hexosamine from B. coagul ans spore integuments is reported. The results show that spore mucopeptide is mainly located in the residual cortex and cortical membrane and suggest that these structures consist essentially of mucopeptide. The implications of these results in relation to the "contractile cortex" theory of heat resistance in spores are discussed.